2007
DOI: 10.1007/s10103-007-0489-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of in vitro dental erosion by optical techniques

Abstract: Nitrogen laser-induced fluorescence (LIF) and tungsten halogen lamp excited diffuse reflectance spectra were recorded in 350- to 700-nm range on a miniature fiber-optic spectrometer from in vitro premolar tooth during various stages of artificial erosion with 36% phosphoric acid. Both the LIF spectral intensity and the diffuse reflectance intensity gradually increased during tooth erosion. The LIF spectra were analyzed by curve fitting using Gaussian spectral functions to determine the true contribution of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies. 19,20 Particularly, sharp decay of the specular reflection was observed already in the early stages of enamel erosion in vitro, while the less pronounced increase of the diffuse reflection intensity was measured, which correlated well with the results of Thomas et al 17 Further investigation revealed a strong correlation between the decrease of the specular reflection and continuous surface roughening. 19 Significant change of the specular reflection was detected even in eroded and abraded surfaces.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies. 19,20 Particularly, sharp decay of the specular reflection was observed already in the early stages of enamel erosion in vitro, while the less pronounced increase of the diffuse reflection intensity was measured, which correlated well with the results of Thomas et al 17 Further investigation revealed a strong correlation between the decrease of the specular reflection and continuous surface roughening. 19 Significant change of the specular reflection was detected even in eroded and abraded surfaces.…”
Section: Introductionsupporting
confidence: 89%
“…Fried et al demonstrated a new near-infrared (IR) reflectance imaging method 15,16 which could be potentially used for the clinical localization of the demineralized tissue. Thomas et al showed a gradual increase of the diffuse reflectance during tooth erosion, 17 though the sensitivity of the signal to erosive changes was poor. Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…The low sensitivity of the diffuse reflection analysis for in vitro erosion assessment was found in the former study 17 and was mentioned in another publication as well. 10 …”
Section: Assessment Of Erosion Progression By Reflection Analysis Of mentioning
confidence: 99%
“…Often, significant erosive tooth wear induces tooth hypersensitivity and requires expensive restorative therapies. 9 To improve the situation, much attention has been given to the development of new techniques, [10][11][12][13][14][15] which provide a quantitative assessment of dental erosion. Among the different varieties, optical diagnostic tools have certain advantages due to their noninvasive and nondestructive evaluation of dental tissues, and fast signal acquisition and data analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation